Using an Interactive Systems Framework to Expand Telepsychology Innovations in Underserved Communities - Whitney R. Garney; Carly E. McCord; Michaela V. Walsh; Angela B. Alaniz (Scientifica)
Literature indicates that the use of promising innovations in mental health care can be improved. The advancement of telepsychology is one innovation that has been utilized as a method to reduce rural health disparities and increase the number of people with access to mental health services. This paper describes a successful pilot telepsychology program implemented in a rural community to increase access to mental health services and the model’s replication and expansion into four additional communities using concepts described in an Interactive Systems Framework. The Interactive Systems Framework highlights how building local capacity specific to organizational functioning and innovations are necessary to support, deliver, and disseminate innovations within new settings. Based on the knowledge gained from this telepsychology innovation, the application of an Interactive Systems Framework and funding mechanisms are discussed.